2006
DOI: 10.1097/01.ogx.0000228717.81730.5b
|View full text |Cite
|
Sign up to set email alerts
|

Ropinirole in the Treatment of Patients With Restless Legs Syndrome: A US-Based Randomized, Double-Blind, Placebo-Controlled Clinical Trial

Abstract: Injury of the ureter or bladder is one of the more serious complications of hysterectomy, and three fourths of ureteral injuries are associated with gynecologic operations. Most injuries involve the lower 3 cm of the ureter, and they usually are one-sided.This study is a retrospective review of ureteral injuries that occurred in the past 7 years in conjunction with total laparoscopic hysterectomy (TLH), performed in 106 women, or subtotal LH (STLH) in 232. Ureteral injuries were diagnosed by postoperative vagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(75 citation statements)
references
References 0 publications
4
70
1
Order By: Relevance
“…20 The reductions in IRLS total score observed in the present study are also comparable with those reported for dopamine agonists that are currently approved for treatment of RLS. [31][32][33][34][35] A significant mean reduction in IRLS total score from baseline was also reported with GEn 600 mg (-13.8) compared with placebo (-9.8), and a greater proportion of GEn 600 mg-treated subjects were rated by investigators as CGI-I responders (72.8% compared with 44.8%, respectively). These results contrast with findings from a 2-week study of GEn 600 mg reported by Walters et al that demonstrated a nonsignificant mean reduction from baseline in IRLS total score at Week 2 LOCF (-9.1) compared with placebo (-8.9), and no significant difference in the proportion of CGI-I responders (GEn 600 mg, 58.6%; pla- jects in the present study reported significant sleep disturbance at baseline on the MOS Sleep Scale domains compared with a healthy cohort sample of the US population.…”
Section: Discussionmentioning
confidence: 99%
“…20 The reductions in IRLS total score observed in the present study are also comparable with those reported for dopamine agonists that are currently approved for treatment of RLS. [31][32][33][34][35] A significant mean reduction in IRLS total score from baseline was also reported with GEn 600 mg (-13.8) compared with placebo (-9.8), and a greater proportion of GEn 600 mg-treated subjects were rated by investigators as CGI-I responders (72.8% compared with 44.8%, respectively). These results contrast with findings from a 2-week study of GEn 600 mg reported by Walters et al that demonstrated a nonsignificant mean reduction from baseline in IRLS total score at Week 2 LOCF (-9.1) compared with placebo (-8.9), and no significant difference in the proportion of CGI-I responders (GEn 600 mg, 58.6%; pla- jects in the present study reported significant sleep disturbance at baseline on the MOS Sleep Scale domains compared with a healthy cohort sample of the US population.…”
Section: Discussionmentioning
confidence: 99%
“…Ropinirole IR has been evaluated in multiple randomized, placebo-controlled trials. These studies uniformly demonstrate that ropinirole is an effective treatment for RLS, improving RLS symptoms, sleep, and quality of life [80][81][82][83][84]. Improvement with ropinirole occurred approximately 1 week after the initiation of therapy.…”
Section: Dopamine Agonists For Rlsmentioning
confidence: 99%
“…Details of the placebo analysis of 12 RLS drug trials [17][18][19][20][21][22][23][24][25][26][27][28] and the two VS trials 4,29 have been previously published. Controls for the drug trials were pharmacologically inert pills identical in appearance to study drugs.…”
Section: Trials Selectedmentioning
confidence: 99%